Fingerprint ATM based system / Muhammad Fitri Mohammad Zainurlah - Mohammad Zainurlah, Muhammad Fitri (2021)
ATM systems are no longer secure since certain hackers are capable of gaining access to ATM accounts of consumers seeking ATM services. In order to make people's ATM accounts more secure, we're launching a new finger print module that will more precisely authenticate the actual user. As a result, hackers will be unable to access the persona accounts of many persons. As a result, hackers will be unable to access the persona accounts of many persons. The main goal of this project is to investigate the method that is used for more secure ATM cash withdrawals. Bankers will capture the customer's finger prints and mobile number while opening the account, and only the consumer will be able to use the ATM machine.